Beecham House [videorecording (DVD)] - Chadha, Gurinder; Shahrukh Husain; Berges, Paul Mayeda (Masterpiece theatre (Television program), 2020)
"Delhi, 1795. John Beecham, a former soldier in the East India Company, is determined to leave the past behind him and start a new life. When he arrives at the grand house, the staff are shocked to discover that their secretive new master has arrived with his infant son August, a baby of mixed parentage. John is determined to reunite his family in Delhi and keep the identity of his child secret, but at what cost to himself and those he loves?"--